Стратегії й тактики англомовного дипломатичного дискурсу (на матеріалі промов держсекретаря США Дж. Керрі) - Судус, Юлія Василівна; Sudus, Y. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті йдеться про дипломатичний дискурс та його сутність, окреслено його загальні аспекти. Проаналізовано дефініції термінів мовна «стратегія» і «тактика» та досліджено погляди науковців на визначення цих понять. Розглянуто засоби впливу за мета-моделлю НЛП Р. Бендлера та Дж. Гріндера як тактики стратегії дискредитації. Проаналізовано особливості реалізації дискурсивних тактик англомовного дипломата. На прикладі сучасних промов дипломата США Джона Керрі простежено використання досліджуваних мовних тактик. The article deals with diplomatic discourse and its essential characteristics. Verbal definitions of the terms strategy and tactics are analyzed and the views of several scientists regarding the definition of these concepts are considered. This article involves the topic of «influencing mean», based on the NLP meta-model developed by Richard Bandler and John Grinder, and examines them as tactics of discrediting strategy. The article contains examples taken from contemporary speeches given by current U.S. Secretary of State John Kerry on August 26 and August 30, 2013 which illustrate the use of the speech tactics being investigated. The examples illustrate the high frequency of the use of different speech tactics in diplomatic discourse which have the single goal of implementing the communicative intention of the speaker, and in that way utilizing a discrediting strategy.
Strategіes and tactics of English-speaking diplomatic discourse (based on speeches given by U.S. Secretary of State John Kerry)
Keywords: дипломатичний дискурс; diplomatic discourse; комунікативна стратегія; communication strategy; комунікативна тактика; communication tactics